The active librarian ([Canton Public Library], 2015)
"Public librarians in particular must acquire a wide-ranging set of skills and talents: outreach and marketing, computer networking, digital literacy instruction, collection development, and much, much more. This publication reports on concrete, specific initiatives, services, programs, and protocols for public libraries. They provide clear explanations for these proposals with the intention of being repeatable by other public librarians. In short, another library should be able to take the information in our articles and use it to develop, implement, or enhance its own service. Ultimately The Active Librarian aims to enhance the profession by publishing needed program analysis and assessment. "
Keywords: Public libraries : Periodicals; Public libraries : Administration : Periodicals; Public libraries; Public libraries : Administration